2017
DOI: 10.1186/s12992-017-0252-6
|View full text |Cite
|
Sign up to set email alerts
|

A health partnership to reduce neonatal mortality in four hospitals in Rwanda

Abstract: BackgroundA health partnership to improve hospital based neonatal care in Rwanda to reduce neonatal mortality was requested by the Rwandan Ministry of Health. Although many health system improvements have been made, there is a severe shortage of health professionals with neonatal training.MethodsFollowing a needs assessment, a health partnership grant for 2 years was obtained. A team of volunteer neonatologists and paediatricians, neonatal nurses, lactation consultants and technicians with experience in Rwanda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 5 publications
1
34
0
Order By: Relevance
“…In order to target limited resources toward improving outcomes, we performed a chart review of a national referral NICU in Haiti to ascertain areas for targeted interventions. Similar chart reviews in other low and mid income countries (LMICs), such as Uganda [12] have been performed and have shown that evaluation of current practices may lead to decreased mortality in low resource settings such as in Rwanda [13]. The differences in characteristics observed between the neonates who died in the NICU and those that survived to discharge suggest specific patterns of neonatal morbidity and mortality.…”
Section: Discussionmentioning
confidence: 77%
“…In order to target limited resources toward improving outcomes, we performed a chart review of a national referral NICU in Haiti to ascertain areas for targeted interventions. Similar chart reviews in other low and mid income countries (LMICs), such as Uganda [12] have been performed and have shown that evaluation of current practices may lead to decreased mortality in low resource settings such as in Rwanda [13]. The differences in characteristics observed between the neonates who died in the NICU and those that survived to discharge suggest specific patterns of neonatal morbidity and mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Although there is evidence for persistently high mortality despite training in certain developing countries, 7 it is shown in university hospitals as well as district hospitals in Rwanda that mortality can be reduced by providing intensive neonatal training. 8 Significant improvements in knowledge have been shown for team training in obstetric and neonatal emergencies using highly realistic simulation in Mexico. 9 This corresponds to the intention of our combined obstetric and pediatric teaching setting, although this may be difficult to quantify.…”
Section: Discussionmentioning
confidence: 99%
“…During phase 2, a literature review was conducted on existing neonatal competency frameworks, and those included were the Royal College of Nursing (UK), [7] Rwandan Competency Framework, [8] Scottish Neonatal Nurses' Group, [9] Australian College of Neonatal Nurses [10] and the Pan-London Band 5 Competency Document. [11] Through a process of inductive and deductive reasoning, the competencies were formulated as an abridged list of competencies and verified by seven neonatal nursing experts through the Delphi technique.…”
Section: Phasementioning
confidence: 99%
“…[6] Several neonatal competency frameworks have been developed over time. [7][8][9][10][11] In developed countries, neonatal competencies seem to have comparable domains such as using research and evidence, leadership and professional development, communication, and legal and ethical considerations. [7,[9][10][11] None of these could be applied directly to the SA context, since neonatal care takes place in a variety of settings.…”
mentioning
confidence: 99%